A brief report on workshop on ultrasound therapy and ultrasonic power measurement - V. N. BINDAL (Archives of Acoustics)
A one day Workshop and Exhibition on Ultrasound Therapy and Ultrasonic Power Measurement was organised on 14th Feb. 1983 by Ultrasonic Society of India (USI) in collaboration with National Physical Laboratory, New Delhi and Delhi Productivity Council at National Physical Laboratory, New Delhi-110012. The purpose of the Workshop was to discuss the significance of calibration procedures of ultrasonic power output and frequency for therapeutic applications by bringing together the medical doctors, physicists, and engineers on a common forum. The subjects covered in the workshop included various aspects of ultrasonic therapy, calibration procedures for characterizing output of therapeutic devices and the most important of all were the future recommendations.